Structure of the Transmembrane Domain of HIV-1 Envelope Glycoprotein - Chen, Bing (FEBS J, 2016)
HIV-1 envelope spike (Env) is a heavily glycosylated, type I membrane protein that mediates fusion of viral and cell membranes to initiate infection. It is also a primary target of neutralizing antibodies and thus an important candidate for vaccine development. We have recently reported an NMR structure of the transmembrane (TM) domain of HIV-1 Env reconstituted in a membrane-like environment. Taking HIV-1 as an example, we discuss here how a TM domain can anchor, stabilize and modulate a viral envelope spike and how its high-resolution structure can contribute to understanding viral membrane fusion and to immunogen design.